The effect of effort and ethical orientation on audit judgment performance - Abdul Rahman, Rashidah; Omar, Normah; Mohd Sanusi, Zuraidah; Johari, Razana Juhaida (2011)
A continuity of global corporate failures (e.g. Lehman Brothers, 2008; Enron, 2001; and WorldCom, 2002 in the US; BCCI, 1991; Barring Bank, 1995 in the UK) and a series of corporate scandals in Malaysia (starting with Perwaja Steel, 1997 and up to Sime Darby, 2010), have severely damaged public perceptions on auditors' judgment performance. The quality of auditors' judgments is being argued and has resulted in an erosion of the public's confidence towards the auditing profession. Audit judgments involve the professional judgments of independent auditors in their audit work (Gibbins, 1984). Professional judgments reflect the collective judgments of all stages of audit work which are audit planning, collection and evaluation of audit evidence and formation of audit opinion. The failure of a number of large companies without auditors warning raised serious questions about the quality and reliability of audited information (Cadbury, 1992). In order to restore public confidence in the profession and to increase the quality of audit judgment, regulators have embarked on a number of measures. Therefore, in the name of public benefit, regulators across the globe have stepped up their scrutiny of the accounting profession and have released federal laws (such as Sarbanes-Oxley Act 2002 in US and Malaysian Code of Corporate Governance 2000, revised 2007 in Malaysia) and new auditing standards (e.g. Statement of Auditing Standard 99, 2002 and International Standard on Quality Control I, 2006). The new laws and auditing standard are primarily aimed at providing more guidance on auditing issues for the auditors in exercising their duties effectively. However, despite the availability of listed laws and standards in the market, one cannot stop to wonder if the basic requirement of those performing auditors is associated with skills, competencies and responsibilities of each individual auditor. Indeed, the public's